Synthesis, Characterization, Density Functional Theory Analyses And Nonlinear Optical Properties Of New Chalcone Derivatives - Zainuri, Dian Alwani (2020)
A series of new anthracenyl chalcone compounds were successfully synthesized using Claisen Schmidt condensation method. These anthracenyl chalcone derivatives structures have been determined and refined using X-ray single crystal diffraction data and optimized at the ground state using density functional theory (DFT) method. The compounds were then characterized by using FTIR, NMR and UV-Vis methods. The presence of functional group and the number of carbon and proton in the molecular structure are confirmed by FTIR and NMR spectroscopy, respectively. The UV-Vis spectrum shows all chalcones have higher maximum wavelength (386-422 nm) and good transparency window for optical application. The experimental spectroscopic data were compared with the theoretical DFT spectra, where the values show good agreement. The existences of intermolecular hydrogen bonds in all compounds play important roles in their packing pattern and NLO properties. All the compounds show a good HOMO-LUMO energy gap values which indicate potential for optoelectronic applications. The molecular electrostatic potential (MEP) identifies the positive, negative and neutral electrostatic potential regions of the molecules. The difference substituents to the anthracenyl chalcone affect the dipole moments and NLO response of the compounds. The nonlinear absorption coefficient (β) and nonlinear refractive index (n2) have been evaluated from the open aperture and closed aperture Z-scan. Based on the measured nonlinear susceptibility χ3, all structures offers great potential in applications such as optical switching and optical limiting applications.